Cross-cultural adaptation and validation of the 12-item Multiple Sclerosis Walking Scale (MSWS-12) for the Brazilian population - Bruna E. M. Marangoni; Karina Pavan; Charles Peter Tilbery (Arquivos de Neuro-Psiquiatria)
Gait impairment is reported by 85% of patients with multiple sclerosis (MS) as main complaint. In 2003, Hobart et al. developed a scale for walking known as The 12-item Multiple Sclerosis Walking Scale (MSWS-12), which combines the perspectives of patients with psychometric methods. OBJECTIVE: This study aimed to cross-culturally adapt and validate the MSWS-12 for the Brazilian population with MS. METHODS: This study included 116 individuals diagnosed with MS, in accordance with McDonald's criteria. The steps of the adaptation process included translation, back-translation, review by an expert committee and pretesting. A test and retest of MSWS-12/BR was made for validation, with comparison with another scale (MSIS-29/BR) and another test (T25FW). RESULTS: The Brazilian version of MSWS-12/BR was shown to be similar to the original. The results indicate that MSWS-12/BR is a reliable and reproducible scale. CONCLUSIONS: MSWS-12/BR has been adapted and validated, and it is a reliable tool for the Brazilian population.